Instructional Supervision Practices in Tanzanian Public Pre-primary Classes: Head Teachers and Pre-primary Teachers ' Perspectives - Zadock, Awino Joseph (Papers in Education and Development, 2023)
The study aimed to find out teachers ' perspectives about school-based instructional supervision practices for improving teaching skills among pre-primary teachers. Qualitative approach was used with a case study design. Data were obtained from sixteen participants using interview and documentary review. Thematic data analysis process was used. The study unveiled that head teachers ' instructional supervision practices were not effectively done. Head teachers were lacking appropriate supervision skills for pre-primary classes. Conversely, pre-primary teachers wanted supervisors to conduct pre and post instructional supervision discussion. Besides, there were no formal arrangements for teachers to learn new teaching strategies. The study suggests that instructional supervision process should be in a collaborative way on a regular basis. This could be achieved through mentoring, coaching, teaming, clinical supervision and professional growth plans. It is recommended that head teachers should be trained regularly for effective supervision of pre-primary curriculum. Keywords: collaborative practices, instructional supervision, preprimary education, teaching skills